13 minutes [videorecording (DVD)] - Gossling, Lindsay; Gossling, Lindsay; Gossling, Lindsay; Adkins, Trace; Birch, Thora; Facinelli, Peter, 1973- (Quiver Distribution, 2021)
Follows four families in the Midwest who have thirteen minutes to get to shelter before a devastating tornado comes through their town.